Shipping is a people's business : a study of human element in container shipping industry - Oh, Jun Kai (2016)
Many studies in the past have been conducted to analyse the People factor in shipping industry. However, there is actually still limited study conducted to compare and evaluate the importance of shore-based human, software and hardware specifically in container shipping industry. Hence, this study aims to bridge the gap in that aspect in the first part of the study and will also establish some of the People factors that are important for companies to manage in the second part.